Delirium in Older Patients after Combined Epidural–General Anesthesia or General Anesthesia for Major Surgery: A Randomized Trial. (August 2021) - Li, Ya-Wei; Li, Huai-Jin; Li, Hui-Juan; Zhao, Bin-Jiang; Guo, Xiang-Yang; Feng, Yi; Zuo, Ming-Zhang; Yu, Yong-Pei; Kong, Hao; Zhao, Yi; Huang, Da; Deng, Chun-Mei; et al.
Abstract : Background: Delirium is a common and serious postoperative complication, especially in the elderly. Epidural anesthesia may reduce delirium by improving analgesia, reducing opioid consumption, and blunting stress response to surgery. This trial therefore tested the hypothesis that combined epidural–general anesthesia reduces the incidence of postoperative delirium in elderly patients recovering from major noncardiac surgery. Methods: Patients aged 60 to 90 yr scheduled for major noncardiac thoracic or abdominal surgeries expected to last 2 h or more were enrolled. Participants were randomized 1:1 to either combined epidural–general anesthesia with postoperative epidural analgesia or general anesthesia with postoperative intravenous analgesia. The primary outcome was the incidence of delirium, which was assessed with the Confusion Assessment Method for the Intensive Care Unit twice daily during the initial 7 postoperative days. Results: Between November 2011 and May 2015, 1, 802 patients were randomized to combined epidural–general anesthesia (n = 901) or general anesthesia alone (n = 901). Among these, 1, 720 patients (mean age, 70 yr; 35% women) completed the study and were included in the intention-to-treat analysis. Delirium was significantly less common in the combined epidural–general anesthesia group (15 [1.8%] of 857 patients) than in the general anesthesia group (43 [5.0%] of 863 patients; relative risk, 0.351; 95% CI, 0.197 to 0.627; P < 0.001; number needed to treat 31). Intraoperative hypotension (systolic blood pressure less than 80 mmHg) was more common in patients assigned to epidural anesthesia (421 [49%] vs . 288 [33%]; relative risk, 1.47, 95% CI, 1.31 to 1.65; P < 0.001), and more epidural patients were given vasopressors (495 [58%] vs . 387 [45%]; relative risk, 1.29; 95% CI, 1.17 to 1.41; P < 0.001). Conclusions: Older patients randomized to combined epidural-general anesthesia for major thoracic and abdominal surgeries had one third as much delirium but 50% more hypotension. Clinicians should consider combining epidural and general anesthesia in patients at risk of postoperative delirium, and avoiding the combination in patients at risk of hypotension. Abstract : In a randomized trial comparing epidural–general anesthesia versus general anesthesia alone in older patients having major surgery, delirium was less common with epidural–general anesthesia. Intraoperative hypotension was more common in the epidural–general anesthesia group.Supplemental Digital Content is available in the text.